Life by the drop: water as a physiological driver of the tallgrass prairie plant community - Nippert, Jesse Brian, author; Knapp, Alan, advisor; Ryan, Michael G., committee member; Blair, John M., committee member; Kelly, E. F., committee member (Colorado State University. Libraries, 2006)
Competition for water is an important driver of community structure and productivity in many grasslands, including North American tallgrass prairies, with nearly two thirds of annual plant productivity allocated belowground. While the root structure was first described nearly 70 years ago, the functional significance of species-specific differences in rooting patterns has only been the subject of speculation. By comparing species differences in water uptake and how these relate to water availability and plant stress, our ability to predict responses to ecosystem drying from climatic variability will likely be enhanced. Using annually-burned watersheds at the Konza Prairie Biological Station, I measured a suite of C4 grasses and C3 woody and forb species to determine how differences in water-use and acquisition may vary among species seasonally and spatially across the landscape. I tested hypotheses related to the extent that inherent physiological differences between photosynthetic pathways (C3, C4) explained patterns of C4 grass dominance in this ecosystem. When carboxylation, electron-transport, and maximum photosynthetic rates were compared between resource-rich and resource limited (ambient) environments, these values declined or remained constant in the C4 grass and C3 forb species, while they increased in C3 legumes. The higher water-use efficiency of C4 species did not facilitate increased rates of carbon capture, as the supply of CO2 remained constant between resource environments, but the demand decreased. These results suggest that resource limitations influenced carbon supply vs. demand of species similarly, regardless of species or photosynthetic pathway. To identify differences in patterns of plant water-uptake, I measured the stable isotope ratio of oxygen in xylem-water, soil water and precipitation to determine the primary depth in the soil profile from which these tallgrass species were acquiring water. Following rainfall events, water was used predominantly from surface soil layers (0-10cm) by all species. However, following 4-6 weeks of drought, C3 species used water from deeper soil layers (>30cm) compared to the C4 grasses. These results were date-independent and were consistent over all topographic positions. When water availability and plant water stress were related to water-used, C3 species relied less on water in surface soil layers (0-10cm) as soils dried and plant water stress increased. Midday water stress of C3 species increased primarily late in the season when plant leaf area was high, but not from decreases in surface soil layer water availability. Conversely, water-use by C4 grasses was invariant to water availability in 0-10cm soil layer or the degree of midday water stress experienced. The best predictor of midday water stress in C4 grasses was surface water availability, suggesting a greater dependence on moisture in shallow soil layers. Water-use, therefore, appears to vary principally between C4 grasses and C3 species based on surface soil layer water availability. This pattern suggests mechanisms of drought tolerance are more important for grasses while drought avoidance is more important for C3 species. These results provide a mechanistic explanation for previously documented responses to experimental changes in precipitation in tallgrass prairie, including increased plant diversity of C3 species and decreased productivity of C4 grasses. Drier surface soil layers from increased variability in hydrometeorological processes reduce productivity in the dominant C4 grass species the most, compared to C3 species with greater belowground niche diversity and the ability to vary water-use based on water availability.
Keywords: ecology